Overcoming blockade in producing doubly excited dimers by a single intense pulse and their decay - Demekhin, Philipp V.; Gokhberg, Kirill; Jabbari, Ghazal; Kopelke, Sören; Kuleff, Alexander I.; Cederbaum, Lorenz S. (Journal of physics. B, Atomic, molecular and optical physics, 2013)
Excitation of two identical species in a cluster by the absorption of two photons of the same energy is strongly suppressed since the excitation of one subunit blocks the excitation of the other one due to the binding Coulomb interaction. Here, we propose a very efficient way to overcome this blockade in producing doubly excited homoatomic clusters by a single intense laser pulse. For Ne2 it is explicitly demonstrated that the optimal carrier frequency of the pulse is given by half of the target state's energy, which allows one to doubly excite more than half of the dimers at moderate field intensities. These dimers then undergo ultrafast interatomic decay bringing one Ne to its ground state and ionizing the other one. The reported ab initio electron spectra present reliable predictions for future experiments by strong laser pulses.
Gesehen am 11.12.2020